CIVIL SOCIETY PERSPEKTIF PENDIDIKAN ISLAM MULTIKULTURAL - Musawir; Sholehuddin Sulaiman (Mu'allim, 2022)
This research examines civil society from an educational perspective. By using qualitative methods, the results of this study state that the basic concepts of Islamic education are relevant to the interests of Muslims and relevant to the design of civil society, so the application of the basic concepts of philosophy and educational theory must pay attention to the supra-system context for the benefit of the civil society that this nation aspires to.